Wonderland creek eaudiobook - Austin, Lynn (Recorded Books Inc., 2012)
Six-time Christy Award winner Lynn Austin has won a loyal following for her inspiring historical fiction. In Wonderland Creek, young Chicago-area librarian Alice Grace Ripley is left heartbroken when her fiancE breaks up with her just as the Great Depression forces her out of a job. To escape the local gossip, Alice volunteers to deliver donated books to a library in rural Kentucky. There she discovers that God still has a plan for her after all.